2013
DOI: 10.1007/s00384-013-1660-6
|View full text |Cite
|
Sign up to set email alerts
|

Perineal reconstruction after extra-levator abdominoperineal excision (eLAPE): a systematic review

Abstract: The paucity of high quality data, suggests that a prospective, randomised trial is needed to determine the ideal technique for perineal reconstruction following eLAPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 37 publications
3
64
1
1
Order By: Relevance
“…Perineal wound complications are among the most common complications of abdominoperineal resection, occurring in 20-58% of cases. 19 While no significant differences were observed between the two patient groups in our study, our findings are generally similar to previous results. 15 With regard to QoL, the mean global health status score for the ELAPE cohort of 79.2 is lower than reported previously.…”
Section: Kamali Sharpe Musbahi Reddy Oncological and Quality Of Life supporting
confidence: 92%
“…Perineal wound complications are among the most common complications of abdominoperineal resection, occurring in 20-58% of cases. 19 While no significant differences were observed between the two patient groups in our study, our findings are generally similar to previous results. 15 With regard to QoL, the mean global health status score for the ELAPE cohort of 79.2 is lower than reported previously.…”
Section: Kamali Sharpe Musbahi Reddy Oncological and Quality Of Life supporting
confidence: 92%
“…Because rigid pelvic structures made a dead space following APR, the perineal wound was vulnerable to postoperative infection and delayed healing due to excessive tension and devascularization. Perineal wound infection, delayed healing, abscess, wound dehiscence and persistent perineal sinus occurred, and the incidence was estimated in the range of 10-40 % [21]. Although extralevator APR showed oncologic superiority, it was reported that perineal wound complications of extralevator APR were twice as higher than conventional APR [9].…”
Section: Discussionmentioning
confidence: 98%
“…Although various wound techniques were developed, we should be reminded that wound healing can be compromised by the high-risk factors such as diabetes, smoking, increased BMI and comorbidities such as inflammatory bowel disease [13,21,23]. Radiation-related perineal complications were reported for short-course and longcourse RT in the previous randomized controlled trials [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 on the other hand, there are concerns of mesh infection, delayed wound healing, mesh exposure in the setting of wound dehiscence and even enterocutaneous fistula formation after repair with both synthetic and biological mesh. 20 Primary flap reconstruction after traditional aPR has been definitively shown to reduce the incidence of complications and need for reoperation. 21 major perineal complications are less common with flap reconstruction (3.5%-15.8%) than with primary closure (25%-46%).…”
Section: Discussionmentioning
confidence: 99%